Cassava Peels for Alternative Fibre in Pulp and Paper Industry: Chemical Properties and Morphology Characterization - Mohd Aripin, Ashuvila; Mohd Kassim, Angzzas Sari; Daud, Zawawi; Mohd Hatta, Mohd Zainuri (International Journal of Integrated Engineering, 2013)
Without a proper waste management, the organic wastes such as cassava peels could result in increased amount of solid waste dump into landfill. This study aims to use non-wood organic wastes as pulp for paper making industries; promoting the concept of ‘from waste to wealth and recyclable material’. The objective of this study is to determine the potential of casssava peel as alternative fibre in pulp and paper based on its chemical properties and surface morphology characteristic. Quantified parameters involved are holocellulose, cellulose, hemicellulose, lignin, one percent of sodium hydroxide, hot water solubility and ash content. The chemical characterization was in accordance with relevant TAPPI Test, Kurscher-Hoffner and Chlorite methods. Scanning electron microscopy (SEM) was used to observe and determine the morphological characteristic of untreated cassava peels fibre. In order to propose the suitability of the studied plant as an alternative fibre resource in pulp and paper making, the obtained results are compared to other published literatures especially from wood sources. Results indicated that the amount of holocellulose contents in cassava peels (66%) is the lowest than of wood (70 - 80.5%) and canola straw (77.5%); however this value is still within the limit suitability to produce paper. The lignin content (7.52%) is the lowest than those of all wood species (19.9-26.22%). Finally, the SEM images showed that untreated cassava peel contains abundance fibre such as hemicellulose and cellulose that is hold by the lignin in it. In conclusion, chemical properties and morphological characteristics of cassava peel indicated that it is suitable to be used as an alternative fibre sources for pulp and paper making industry, especially in countries with limited wood resources